Morphologic and functional alterations in the parasagittal dural space in mild cognitive impairment - Bio Joo; Mina Park; Song Soo Kim; Sung Jun Ahn; Han-Kyeol Kim; Hanna Cho; Chul Hyoung Lyoo; Sang Hyun Suh (Scientific Reports)
Abstract This study aimed to identify morphologic and functional differences in the parasagittal dural space (PSD) between patients with mild cognitive impairment (MCI) and cognitively unimpaired participants using dynamic contrast-enhanced MRI (DCE MRI). A total of 29 MCI patients and nine controls underwent structural MRI and DCE MRI, where PSD volume and parameters such as peak wash-in rate and time to first peak enhancement were assessed. MCI patients had significantly larger PSD volume (P = 0.023), a lower peak wash-in rate (P < 0.001), and delayed time to first peak (P = 0.001) compared to controls. In multivariate regression analysis, PSD volume (β = -0.579, 95% CI [-1.072 – -0.086], P = 0.023) and wash-out rate (β = -3.293, 95% CI [-6.351 – -0.235], P = 0.036) were significantly associated with the Mini-Mental State Examination (MMSE) score. Additionally, a lower peak wash-in rate correlated significantly with lower cognitive performance, as measured by the Montreal Cognitive Assessment (MoCA) (P = 0.043). This association highlights a potential link between meningeal lymphatic dysfunction and cognitive decline, suggesting that PSD alterations could reflect early stages of neurodegenerative changes. In conclusion, these PSD structural and functional alterations in MCI patients may serve as early imaging markers, helping in the assessment of disease severity in neurodegenerative conditions such as Alzheimer’s disease. This insight into meningeal lymphatic dysfunction provides a promising direction for early diagnosis and monitoring of cognitive impairment.